Gas Sensing with Solar Cells: The Case of NH(3) Detection through Nanocarbon/Silicon Hybrid Heterojunctions - Drera, Giovanni (Nanomaterials (Basel), 2020)
Photovoltaic (PV) cells based on single-walled carbon nanotube (SWCNT)/silicon (Si) and multiwalled carbon nanotube (MWCNT)/Si junctions were tested under exposure to NH(3) in the 0–21 ppm concentration range. The PV cell parameters remarkably changed upon NH(3) exposure, suggesting that these junctions, while being operated as PV cells, can react to changes in the environment, thereby acting as NH(3) gas sensors. Indeed, by choosing the open-circuit voltage, V(OC), parameter as read-out, it was found that these cells behaved as gas sensors, operating at room temperature with a response higher than chemiresistors developed on the same layers. The sensitivity was further increased when the whole current–voltage (I–V) curve was collected and the maximum power values were tracked upon NH(3) exposure.